Fermentation parameter optimization of microbial oxalic acid production from cashew apple juice - Betiku, Eriola (Heliyon, 2016)
The potential of cashew apple juice (CAJ) as a carbon source for oxalic acid (OA) production via fermentation process was investigated in this study. The effects and interactions of CAJ concentration, time, pH, NaNO(3) concentration and methanol concentration on OA production were determined in a central composite design (CCD) and the process was modelled and optimized using response surface methodology (RSM). The results showed that OA fermentation can be described significantly (p < 0.05) by a quadratic model giving regression coefficient (R(2)) of 0.9964. NaNO(3) concentration was the most significant positive variable while methanol was not a significant variable. A maximum OA concentration of 122.68 g/l could be obtained using the optimum levels of CAJ of 150.0 g/l, pH of 5.4, time of 7.31 days, NaNO(3) of 2 g/l and methanol of 1% volume. The production of OA was found to increase from 106.75 to 122.68 g/l using the statistically design optimization. This study revealed that CAJ could serve as an inexpensive and abundant feedstock for fermentative OA production, the resulting model could be used in the design of a typical pilot plant for a scale up production.